PERSEPSI TENTANG PRAKTEK KESETARAAN GENDER PADA KARYAWAN CV MILZAM MULTI SEJAHTERA JEMBER - Widayanti, Nike; Hidayat, Nurul; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2019)
The purpose of this research is to describe the practice of gender equality for employees the CV Milzam Multi Sejahtera plywood factory in Jember. The method that used is a qualitative method with a feminist social science approach. Determination of informants used purposive techniques, with criteria namely workers who were working in factories and workers who had worked for at least 1 year. Data collection techniques are carried out by observation, in-depth interviews, and documentation. The validity test of the data uses triangulation techniques. The analysis technique used the interactive models of Miles and Huberman. The theory that used is the Marxist / Socialist feminist theory. The results of the research show that: 1) In the system of division of labor because women are considered to have carefully nature, they are given an easy job, but require precision. While the job for men needs heavy labor. 2) In the salary system, women are considered as cheap labor, so they deserve a cheap salary. This is because women are considered as a side job. 3) The right to leave. Giving leave rights to workers is no different. However, workers who are licensed do not provide replacement salary. 4) Promotion of positions. The promotion of position can be obtained by anyone according to the requirements in the appointment of positions. So, based on the results of the research that in the CV Milzam Multi Sejahtera Jember plywood factory there was no gender inequality, but gender equality practices occurred.   Keywords: Perception, practice equality, gender, workers, factory